THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN THE ZENIUS LEARNING APPLICATION - Dewi Puspaningtyas Faeni; Meri Henni Goretti Sitohang (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to explore the role of Management Information Systems (SIM) in increasing the effectiveness of the use of Zenius learning applications. SIM is an important framework in data and information management, supporting the decision-making process and overall operations of the organization. In the context of Zenius learning apps, SIM plays an important role in managing user data, optimizing learning content, and improving the overall user experience.